Comparing Political Communication: Theories, Cases, and Challenges (Cambridge, 2004)
This volume assesses comparative political communication research and considers potential ways in which it could and should develop. Twenty experts from Europe and the United States offer a unique and comprehensive discussion of the theories, cases, and challenges of comparative research in political communication. The first part discusses the fundamental themes, concepts and methods essential to analyze the effects of modernization and globalization of political communication. The second part offers a broad range of case studies that illustrate the enormous potential of cross-national approaches in many relevant fields of political communication. The third part paves the way for future research by describing the most promising concepts and pressing challenges of comparative political communication. This book is intended to introduce new students to a crucial, dynamic field as well as deepening advanced students' knowledge of its principles and perspectives.